Physical and Chemical Approaches of Photovoltaic Parameters in Dye-Sensitized Solar Cells to ZnO/ZnS:rGO-Based Photoelectrodes - Thiago Kurz Pedra; Ramon Dadalto Carvalho; Cristian Dias Fernandes; Luciano Timm Gularte; Carolina Ferreira de Matos Jauris; Eduardo Ceretta Moreira; Mateus Meneghetti Ferrer; Cristiane Wienke Raubach; Sérgio da Silva Cava; Pedro Lovato Gomes Jardim; Elson Longo; Mario Lucio Moreira (Applied Sciences)
This study proposes an alternative process for obtaining ZnO/ZnS:rGO heterostructures for use in DSSCs and as promising materials for potential applications in other photonic process, such as photocatalysis and photodetection. The compound was obtained through a microwave-assisted hydrothermal method, where the electromagnetic waves and temperature were crucial points for forming ZnO, ZnO/ZnS and reducing graphene oxide (GO). The XRD, Raman, FT-IR, and FESEM results presented the structural, morphological, and chemical structures, which suggest the conversion of ZnO to ZnS for samples with higher concentrations of reduced graphene oxide (rGO). Additionally, the optical properties were analyzed through photoluminescence and UV-Vis measurements. The electrical behavior of the photoelectrodes was investigated through J-V measurements in light and dark conditions. In addition, electrochemical impedance spectroscopy (EIS) was performed and Bode phase plots were created, analyzing the recombination processes and electron lifetime. The J-V results showed that for smaller amounts of rGO, the dye-sensitized solar cells (DSSC) efficiency improved compared to the ZnO/ZnS single structure. However, it was observed that with more significant amounts of rGO, the photocurrent value decreased due to the presence of charge-trapping centers. On the other hand, the best results were obtained for the ZnO/ZnS:1% rGO sample, which showed an increase of 14.2% in the DSSC efficiency compared to the pure ZnO/ZnS photoelectrode.